Effects of Different Drying Temperature and Slice Thickness on Hot Air Drying Characteristics and Quality of Black Garlic - Xiangli LI; Ting WANG; Beibei WANG; Haixiang WEI; Hong CHENG; Jing LIU (Shipin gongye ke-ji, 2025)
In order to investigate the effects of drying temperature and slice thickness on the hot air drying characteristics and quality of black garlic, the drying characteristics, effective moisture diffusion coefficient, and drying kinetics model of black garlic slices were studied at different hot air drying temperatures (50, 60, 70, 80 ℃) and different slice thicknesses (3, 5, 7, 9 mm). The rehydration ratio, color, total phenol content, DPPH· scavenging rate, texture characteristics, and flavor of black garlic slices were analyzed in this experiment. The results showed that the higher the drying temperature and the thinner the slices, the faster the drying rate of black garlic slices. The effective moisture diffusion coefficient ranged from 3.83383×10−9 to 20.47548×10−9 m2/s. The hot air drying process of black garlic slices could be accurately described with Page model (R2=0.9993). The black garlic slices with 5 mm slice thickness were dried for 11.5 h at 70 ℃ hot air temperature, which could obtain higher drying rate and better dry quality. The black garlic slices dried under the above drying conditions showed lower color difference ΔE (8.213) and hardness (62.197 N), higher total phenol content (4.742 mg/g) and DPPH· scavenging rate (83.297%), moderate elasticity (1.908) and adhesiveness (840.356 N). The rehydration ratio of black garlic slices was not significantly affected by the drying temperature. The flavor differences of black garlic slices obtained under different drying conditions could be effectively distinguished by electronic nose.